Processing of land 4D seismic data in case of limited area of repeated survey - a case study from Otway Basin, Australia - Shulakova, V.; Pevzner, Roman; Urosevic, Milovan (EAGE, 2009)
Time lapse 3D seismic is an important part of monitoring and verification program of the Otway Project - an Australian first demonstration of the deep geological storage of CO2 located on-shore in Victoria. From March, 2008 CO2-rich gas is being injected into a depleted gas reservoir at a depth of around 2050 metres. In year 2000 3D pre-production seismic data were acquired over large area, covering Naylor field, our CO2 sequestration site and also several adjacent small gas fields. Baseline 3D seismic data were acquired in December 2007, however due to logistical problems and cost of the survey size of the area was much smaller (only 3 sq. km). Processing of land time-lapse seismic surveys is a challenging task and in this case it was additionally complicated since limited migration aperture was determined to be one of main problems affecting imaging of the target horizon. To overcome this limitation we adopted an approach which is based on joint processing of two different 3D vintage sets with different size of survey area.